Nanoparticles of Kalakai Leaf (Stenochlaena Palustris) and Lemon (Citrus Limon) to Changes Hemoglobin, Erythrocyte and Hematocrit Levels in Adolescent Women - Oktadiarini, Dwi; Isnawati, Muflihah; Wahyuni, Sri (Sarana Ilmu Indonesia (salnesia), 2024)
The prevalence of anemia increases every year, this must be welcomed with innovations in preventing anemia in adolescents so that it does not increase the rate of increase in cases of anemia in adolescents and even pregnancy. One way to treat anemia is to use kalakai and lemon leaves which are processed into nanoparticles. Kalakai leaves contain iron, vitamin C which functions to increase hemoglobin, erythrocyte and hematocrit levels. This research aims to analyze the effect of kalakai leaf and lemon nanoparticles on increasing hemoglobin, erythrocyte and hematocrit levels in adolescent girls. This type of research is true experiment with simple random sampling technique. The total sample was 34 anemic adolescent girls, 17 samples from the intervention group and 17 samples from the control group. This research used kalakai leaf nanoparticles (2g) and lemon (3g) combined together and given once a day for 14 days. The research was conducted at STIKes Borneo Scholar Medika. The administration of kalakai and lemon leaf nanoparticles can significantly increase hemoglobin levels with a p-value=0,000 and an effect size value of 0,66 (Modest Effect) and a percentage in the intervention group of 11,1%, erythrocytes with a p-value=0,000 and an effect size of 0,82 (Modest Effect) and the percentage in the intervention group was 23,4%, Hematocrit value was p=0,000 and the effect size was 0,60 (Modest Effect) and the percentage in the intervention group was 7,6%.